The communication of Islamic information by Shariah-compliant companies in Malaysia - Che Adam, Noriah; Lode, Nor Asma (American Scientific Publishers, 2015)
An increase of information consciousness about Islamic related activities among Muslim community motivates this study to investigate the status and determinants of Islamic information disclosed by Shariah-compliant companies in Malaysia.This study finds that Malaysian companies are interested to release information about saddaqa/donation, the safety/quality of the product, preservation of environment and safety workplace.However, Malaysian companies are reluctant to inform their stakeholder about zakat, waqf and the halal status of their products.This study also indicates that female directors and the proportion of Muslim directors influence the communication of certain Islamic information in the annual report.